2013
DOI: 10.6061/clinics/2013(06)21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the administration of a catalase inhibitor into the fourth cerebral ventricle on cardiovascular responses in spontaneously hypertensive rats exposed to sidestream cigarette smoke

Abstract: OBJECTIVE:Previous studies have demonstrated a relationship between brain oxidative stress and cardiovascular regulation. We evaluated the effects of central catalase inhibition on cardiovascular responses in spontaneously hypertensive rats exposed to sidestream cigarette smoke.METHODS:Male Wistar Kyoto (WKY) rats and spontaneously hypertensive rats (SH) (16 weeks old) were implanted with a stainless steel guide cannula leading into the fourth cerebral ventricle (4th V). The femoral artery and vein were cannul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…It is suggested that the mechanism involved in cardiac autonomic responses induced by auditory stimulation occurs through several pathways, which may include the startle reflex response that is regulated by a brainstem circuit. [ 24 ] The acoustic startle reflex, an effect known on cardiovascular physiology induced by loud sounds, is cited as a sudden rise in arterial BP and HR to abruptly loud sound stimuli. [ 24 ] The intensity used to cause a startle reflex is approximately 110 dB, an intensity that is much higher than that used in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the mechanism involved in cardiac autonomic responses induced by auditory stimulation occurs through several pathways, which may include the startle reflex response that is regulated by a brainstem circuit. [ 24 ] The acoustic startle reflex, an effect known on cardiovascular physiology induced by loud sounds, is cited as a sudden rise in arterial BP and HR to abruptly loud sound stimuli. [ 24 ] The intensity used to cause a startle reflex is approximately 110 dB, an intensity that is much higher than that used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] The acoustic startle reflex, an effect known on cardiovascular physiology induced by loud sounds, is cited as a sudden rise in arterial BP and HR to abruptly loud sound stimuli. [ 24 ] The intensity used to cause a startle reflex is approximately 110 dB, an intensity that is much higher than that used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is responsible for nearly five million annual deaths, and 600,000 people die each year from exposure to second‐hand smoke (Ghasemian et al, ). Many studies demonstrated that cigarette smoke disrupts multiple biological systems (Bahl et al, ; Liu, Ding, Zhang, & Ni, ; Starke et al, ; Valenti et al, ). Within the reproductive system (Dechanet et al, ; Esakky, Hansen, Drury, & Moley, ), cigarette smoking affects erectile dysfunction (Chew, Bremner, Stuckey, Earle, & Jamrozik, ), decreases semen quality (Al‐Matubsi et al, ), and induces sperm DNA double‐strand breaks (Fraga, Motchnik, Wyrobek, Rempel, & Ames, ; La Maestra, De Flora, & Micale, ; Marchetti et al, ), DNA adducts (Potts, Newbury, Smith, Notarianni, & Jefferies, ), chromosomal abnormalities (Yauk et al, ), and abnomal plasma membrane integrity (Ramlau‐Hansen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…systems (Bahl et al, 2012;Liu, Ding, Zhang, & Ni, 2014;Starke et al, 2013;Valenti et al, 2013). Within the reproductive system (Dechanet et al, 2011;Esakky, Hansen, Drury, & Moley, 2012), cigarette smoking affects erectile dysfunction (Chew, Bremner, Stuckey, Earle, & Jamrozik, 2009), decreases semen quality (Al-Matubsi et al, 2011), and induces sperm DNA double-strand breaks (Fraga, Motchnik, Wyrobek, Rempel, & Ames, 1996;La Maestra, De Flora, & Micale, 2015;Marchetti et al, 2011), DNA adducts (Potts, Newbury, Smith, Notarianni, & Jefferies, 1999), chromosomal abnormalities (Yauk et al, 2007), and abnomal plasma membrane integrity (Ramlau-Hansen et al, 2007).…”
mentioning
confidence: 99%
“…This system provides afferent and efferent nerves to the heart, i.e., parasympathetic nerves to the atrioventricular and sinus nodes and sympathetic nerves to the myocardium ( 1 ). The influence of the autonomic nervous system on the heart depends on information from the baroreceptors, chemoreceptors, atrial receptors and ventricular receptors, as well as changes in the respiratory, vasomotor, renin-angiotensin-aldosterone thermoregulatory systems ( 1 ), as well as the brainstem ( 2 ). The cardiovascular system is influenced by internal and external factors, including physical exercise ( 3 ).…”
Section: Introductionmentioning
confidence: 99%